Analisis SWOT dalam Menghadapi Persaingan Bisnis pada Penjualan Motor di PT. Tunas Honda Rantepao - Yanti Bartholomeus; Abedneigo.C. Rambulangi; Grace. S.Mengga (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study examines the SWOT analysis in facing the business competition of motorcycle sales at PT. Tunas Honda Rantepao. The purpose of this research is to understand the internal and external conditions of the company and how strategies can be applied to address the existing challenges. The research method used is qualitative, with data collection through interviews and documentation. Data analysis techniques are carried out through data collection, data reduction, and data presentation steps. The results of the study indicate that the rapid advancement of technology poses a challenge for PT. Tunas Honda Rantepao, forcing this motorcycle dealer to continually innovate in its marketing strategy. Based on the analysis of the company's internal and external conditions, a SWOT analysis was conducted to evaluate the strengths, weaknesses, opportunities, and threats faced. From this analysis, various strategic alternatives were identified that can be applied to improve performance and competitiveness of PT. Tunas Honda Rantepao in the motorcycle market, both in terms of utilizing technology, improving service quality, and developing more effective marketing.